THE POTENTIAL OF DIGITAL GAME-BASED LEARNING FOR ENGLISH VOCABULARY ACQUISITION AMONG MALAYSIAN ADOLESCENTS - Nurulhuda Ibrahim; Chan Chun Sheng; Low Kah Yan (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
English is one of the mandatory subjects in primary and secondary school. However, few young Malaysians are proficient in the language, especially those living in rural areas. This study investigates the potential of using a word-search puzzle game as an alternative learning tool for English vocabulary acquisition. A word-search puzzle game was designed and developed. Additional dictionary features, such as words’ definitions, synonyms, antonyms, and pronunciation, are included in the word-search puzzle game. An online survey was conducted to evaluate the game experience (i.e. game flow and game challenge), perceived usefulness, and intention to use the game. The participants of this research comprised of a total of 30 adolescents recruited using convenient sampling among the contacts of the researchers. Participants were asked to install and play the word-search puzzle game before responding to the questionnaire. The findings indicate that the word-search puzzle game indeed has the potential to improve English vocabulary acquisition among adolescents.